Being poor : a Biblical study - Hoppe, Leslie J.; Inderieden, Nancy (Wilmington, Delaware.: : Michael Glazier, 1987)
Brief text and illustrations describe what it means to be poor.
Keywords: Poor -- Juvenile literature; Poverty -- Juvenile literature; Poor; Poverty